„Cyfrowa rodzina”. Współczesne korzyści i zagrożenia w budowaniu relacji międzyludzkich - Szczepańska , Olga (Studia Edukacyjne, 2024)
The purpose of this article is to highlight the benefits and risks in building interpersonal relationships in the context of the family. Thus, the text attempts to define the concept of the digital family. The author focuses on selected benefits and risks of family members participating in virtual reality. The con-cept of the digital family is formulated based on definitions from various fields of social sciences. The author briefly analyses available data on media use by adults, and later discusses the benefits of being part of a digital family in terms of relationships and security, the dangers of excessive participation in virtual reality, as well as the difficulties associated with relationship breakdown and negative use of digital products. The author also presents selected aspects of the changes taking place in modern family relations between generations and develops the topic of exclusion of the oldest generation in terms of information and general awareness of reality.